The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/jeim-08-2019-0222
|View full text |Cite
|
Sign up to set email alerts
|

A big data analytics based methodology for strategic decision making

Abstract: PurposeThe purpose of this paper is to present a novel framework for strategic decision making using Big Data Analytics (BDA) methodology.Design/methodology/approachIn this study, two different machine learning algorithms, Random Forest (RF) and Artificial Neural Networks (ANN) are employed to forecast export volumes using an extensive amount of open trade data. The forecasted values are included in the Boston Consulting Group (BCG) Matrix to conduct strategic market analysis.FindingsThe proposed methodology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 55 publications
1
15
2
1
Order By: Relevance
“…Despite the rapid growth of digital technologies, they stated that industries also face particular challenges in the adoption and effective use of digital technologies, particularly in the case of productivity-enhancing applications. Furthermore, digital technology creates new growth opportunities for businesses and aids them in making strategic decisions that increase their productivity [86]. Similar findings have been discovered by Ellis et al [58], who pointed out that the digital technology such as IoT and cloud computing can capture vital data in analytics to drive end-to-end supply chain improvements.…”
Section: Discussionsupporting
confidence: 68%
“…Despite the rapid growth of digital technologies, they stated that industries also face particular challenges in the adoption and effective use of digital technologies, particularly in the case of productivity-enhancing applications. Furthermore, digital technology creates new growth opportunities for businesses and aids them in making strategic decisions that increase their productivity [86]. Similar findings have been discovered by Ellis et al [58], who pointed out that the digital technology such as IoT and cloud computing can capture vital data in analytics to drive end-to-end supply chain improvements.…”
Section: Discussionsupporting
confidence: 68%
“…This study reported that BDU is not directly linked to SCP and SMEs' performance, which is not consistent with the research work of 1 Özemre and Kabadurmus (2020), Mangla et al (2020), Raguseo (2018) and Akter et al (2016). Özemre and Kabadurmus (2020) highlighted that big data adoption brings new growth opportunities for firms and assist them in strategic decision-making to improve their productivity.…”
Section: Discussioncontrasting
confidence: 63%
“…This study reported that BDU is not directly linked to SCP and SMEs' performance, which is not consistent with the research work of 1 Özemre and Kabadurmus (2020), Mangla et al (2020), Raguseo (2018) and Akter et al (2016). Özemre and Kabadurmus (2020) highlighted that big data adoption brings new growth opportunities for firms and assist them in strategic decision-making to improve their productivity. Similarly, Mangla et al (2020) mentioned that big data adoption is positively linked to project performance of manufacturing organizations, while Raguseo (2018) investigated the relationship between the adoption of big data technologies, risk, benefits and firm performance and found that big data technologies have a positive effect on FP.…”
Section: Discussioncontrasting
confidence: 63%
“…The global market for Big Data estimated at US$70.5 Billion in the year 2020, is projected to reach a revised size of US$243.4 Billion by 2027, growing at a CAGR of 19.4% over the analysis period 2020-2027. (Research and Markets, 2021) In an increasingly borderless global economy, big data plays a crucial role to successfully reap business and marketing opportunities (Chierici et al, 2019;Del Vecchio et al, 2020;Doh et al, 2016;Gnizy, 2019;€ Ozemre and Kabadurmus, 2020;Shamim et al, 2020). It has been witnessed that 91.6% of Fortune 1,000 companies invested in big data associated mechanisms as this investment is required to stay both agile and competitive in the market place (Osborne, 2019).…”
Section: Introductionmentioning
confidence: 99%